On Weakly W_2-Symmetric Manifolds - Shaikh, A. A.; Jana, Sanjib Kumar; Eyasmin, S. (Sarajevo Journal of Mathematics, 2024)
In the present paper we introduce a type of non-flat Riemannian manifold called weakly W_2-symmetric manifolds and study their geometric properties. The existence of such manifolds is shown by several non-trivial examples. 2000 Mathematics Subject Classification. 53B50, 53C35